Predictive Analysis of Health/Physical Fitness in Health-Promoting Lifestyle of Adolescents - Liu, Hao; Liu, Yiwen; Li, Bin (Frontiers in Public Health, 2021)
Objective: To explore the correlation and predictive power of adolescent health physical fitness on their health promoting lifestyle, so as to provide important reference for the reform of middle school physical education classroom teaching. Methods: Taking some junior and senior high school students in Nanchong City of Sichuan Province as the survey objects, stratified random sampling method was used to carry out health fitness test and questionnaire survey, and SPSS17.0, amos21.0 and other statistical analysis software were used to process the relevant data. Results: 1) Male adolescents had 14.4% predictive power for their overall health promoting lifestyle through the combined effects of cardiopulmonary endurance, muscle strength and explosive strength, while female adolescents had 16.8% predictive power for their overall health promoting lifestyle through the combined effects of cardiopulmonary endurance, flexibility and body mass index. 2) 10.0% of the variation in the health promoting lifestyle of men under 14 years old was caused by the combined effects of muscle endurance and muscle strength, while 14.4% of the variation in the health promoting lifestyle of female adolescents was caused by the combined effects of muscle endurance, muscle strength, flexibility and cardiopulmonary endurance. 3) 10.9% and 17.6% of the variation in health promoting lifestyle of male and female adolescents aged between 14 and 17 were caused by the combined effects of cardiopulmonary endurance, muscle strength and flexibility, respectively . 4) 20.7% of the variation in health promoting lifestyle of male adolescents aged 17 years or above was caused by cardiopulmonary endurance, explosive force and muscle endurance, while 16.8% of the variation in health promoting lifestyle of female adolescents was caused by the combined effect of cardiopulmonary endurance, body mass index BMI and muscle endurance. Conclusion: Adolescents' health and physical fitness can significantly predict their health promoting lifestyle, and the predictive power and the typical correlation between them are affected by demographic factors.